Prospects of use of biogas plants in Ukraine (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
Due to the huge territorial potential and a large amount of agricultural land, relatively low population density and relatively with a favorable climate, the country has good initial conditions for the production, trade and use of bioenergy.In recent years, attention to the issues of rational management of agricultural waste in Ukraine has increased significantly, both from the authorities and from the scientific community. The solution to the problem is possible by implementing effective measures for rapid, safe waste processing and obtaining positive economic and environmental effects from the utilization and reuse of raw materials. The problem of effective waste processing and utilization is one of the most acute in the world, the operation of biogas plants is not a simple task. Considering the world experience in using biogas technologies, we are faced with the problem of profitability of biogas plants. Basically, biogas plants are used not so much as a source of energy, but for neutralizing livestock waste and obtaining high-quality organic fertilizer from them.
Keywords: biogas; biogas plants; biomethane; bioenergy; transport fuel; organic fertilizers; renewable energy sources